Indoor pedestrian displacement estimation using Smart phone inertial sensors. (1st January 2012) - Ayub, Shahid; Zhou, Xiaowei; Honary, Soroush; Bahraminasab, Alireza; Honary, Bahram
The embedded inertial sensors in today's Smart phones have added the facility to use them for localisation and tracking applications. The benefit of using them for localisation purpose is that no extra infrastructure is to be installed in contrast to other existing positioning technologies. Inertial navigation only provides the information relative to initial point, so it is suitable for short distance positioning. However, integration of inertial navigation with other positioning technologies can be used for precise localisation. In this paper we introduce a mechanism for indoor pedestrian positioning using a combination of accelerometer and compass. Three different Smart phone placement modes (idle, hand held and listening) are investigated and a comparison of different pedestrian dead reckoning (PDR) techniques is presented.